Proceedings of the Compilation of the Co-Located Workshops on DSM'11, TMC'11, AGERE! 2011, AOOPES'11, NEAT'11, &Amp; VMIL'11 2011
DOI: 10.1145/2095050.2095074
|View full text |Cite
|
Sign up to set email alerts
|

Expressing pipeline parallelism using TBB constructs

Abstract: Task-based libraries such as Intel's Threading Building Blocks (TBB) provide higher levels of abstraction than threads for parallel programming. Work remains, however, to determine how straightforward it is to use these libraries to express various patterns of parallelism. This case study focuses on a particular pattern: pipeline parallelism. We attempted to transform three representative applicationscontent-based image retrieval, compression and video encoding -to pipelines using TBB. We successfully converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Figure 11 shows speedup for dedup in the pthreads, TBB and Swan programming models. While Reed et al demonstrated improved performance of their TBB implementation relative to the pthreads implementation in PARSEC 2.1 [22], our evaluation using PARSEC 3.0 shows that the TBB implementation is slower than the pthreads implementation. The Swan implementation with hyperqueues outperforms the pthread version by at least 12% and up to 30% in the region of 6-8 threads.…”
Section: Dedupmentioning
confidence: 50%
See 2 more Smart Citations
“…Figure 11 shows speedup for dedup in the pthreads, TBB and Swan programming models. While Reed et al demonstrated improved performance of their TBB implementation relative to the pthreads implementation in PARSEC 2.1 [22], our evaluation using PARSEC 3.0 shows that the TBB implementation is slower than the pthreads implementation. The Swan implementation with hyperqueues outperforms the pthread version by at least 12% and up to 30% in the region of 6-8 threads.…”
Section: Dedupmentioning
confidence: 50%
“…However, it requires thoroughly restructuring the input stage in such a way that it can be called repeatedly to produce the next file [22]. To this end, its internal state must be made explicit (i.e., its current position in the traversal of the directory tree) and passed as an argument to the first stage.…”
Section: Number Of Coresmentioning
confidence: 99%
See 1 more Smart Citation